COMPARATIVE PROGNOSTIC VALUE OF CREATINE PHOSPHOKINASE MB AND TROPONIN T IN THE DIAGNOSTICS OF PERIPROCEDURAL MYOCARDIAL DAMAGE - S. A. Akinina (Российский кардиологический журнал, 2012)
Aim. To investigate the link between the levels of creatine phosphokinase MB (CKMB) or troponin T (TrT) and the prognosis in patients with coronary heart disease (CHD), periprocedural myocardial necrosis, or Type 4a myocardial infarction (MI) associated with percutaneous coronary intervention (PCI). Material and methods. The study included 124 CHD patients who underwent planned PCI. The levels of CK-MB and TrT were measured before PCI and 8 and 24 hours after the procedure. Results. After PCI, CK-MB and TrT levels were elevated in 11 (8,9%) and 24 (19,4%) patients, respectively. CK-MB or TrT elevation was less than three-fold, compared to the upper reference limit (URL), in 9 (7,3%) and 18 (14,5%) participants, respectively. In other words, probable periprocedural myocardial necrosis was not confirmed twice as often, based on CK-MB (n=9; 7,3%) vs. TrT criteria. CK-MB or TrT elevation over 3 x URL was registered in 2 (1,6%) and 6 (4,8%) participants, respectively. Therefore, probable Type 4a MI was not confirmed in 4 patients (3,3%) – three times less often, compared to TrT criteria. Over the mean follow-up period of 4,3 years, survival was non-significantly worse in patients with periprocedural CK-MB elevation of <3 or ≥3 x URL, compared to participants with similar TrT elevation (22,2% vs. 5,6% and 50,0% vs. 33,3%, respectively). The combined end-point of cardiac death and MI was also registered more often in patients with CK-MB elevation (33,3% vs. 16,7% and 50,0% vs. 33,3%, respectively), due to the differences in cardiac death rates. Conclusion. Therefore, periprocedural TrT elevation of <3 and ≥3 x URL could be a less reliable predictor of long-term cardiac mortality than similar CK-MB elevation.